Using post-release monitoring data to optimize avian reintroduction programs: a 2-year case study from the Brazilian Atlantic Rainforest - Bernardo, C. S. S. [UNESP]; Lloyd, H.; Olmos, F.; Cancian, L. F. [UNESP]; Galetti, Mauro [UNESP] (Wiley-Blackwell, 2011)
Post-release monitoring data of reintroduced captive-bred birds can be utilized to help optimize future avian reintroduction programs. We present a case study of broad interest to reintroduction and conservation biologists interested in investigating movements and habitat use by reintroduced captive-bred birds. We used radio telemetry to monitor reintroduced captive-bred red-billed curassow Crax blumenbachii at a private reserve, Rio de Janeiro state, Brazil. During August 2006 and October 2008, 25 radio-tagged individuals (15 females and 10 males, all <30 months old) were monitored over a 25-month period. Evaluation of home-range size and habitat use revealed that captive-bred curassows should be released only into forest areas with adequate riverine habitat that are larger than the minimum home-range movements of the proposed population. Curassows also utilized pastureland, cultivated areas and secondary forests, suggesting that the proximity of release sites to such habitats may not be entirely detrimental for future reintroductions. Site fidelity for reintroduced birds was low, and there was a tendency for resident curassows to move away when new cohorts were released into the area. Determining how habitat characteristics, displacement by newly released cohorts, adjustments to their new surroundings or cohort social interactions influence post-release movements of resident birds at release sites over prolonged time frames would improve our knowledge on the impacts of releasing further captive-bred individuals into habitats with extant populations. Critically, the movement patterns of reintroduced curassows identified in this study demonstrate that avian post-release monitoring must be considered over an appropriate time frame and we highlight how different conclusions may be generated depending on the duration of post-release monitoring. It may take more than 2 years for reintroduced captive-bred sub-adults to become established following release and that post-release monitoring of similar duration may not be adequate for large avian species such as Cracids.
Keywords: Crax blumenbachii; radio telemetry; reintroduction; post-release monitoring; habitat use; Atlantic rainforest